2020
DOI: 10.1021/acs.inorgchem.9b03385
|View full text |Cite
|
Sign up to set email alerts
|

Selective Phase Control of Dopant-Free Potassium Sodium Niobate Perovskites in Solution

Abstract: As one of the perovskite families, potassium sodium niobates (K 1−x Na x )NbO 3 (KNN) have been gaining tremendous attention due to their various functional properties which can be largely determined by their crystallographic phase and composition. However, a selective evolution of different phases for KNN with controlled composition can be difficult to achieve, especially in solution chemical synthesis because of its strong tendency to stabilize into orthorhombic phase at conventional synthetic temperature. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…The ICDD database of the three discrete niobate phases (NaNbO 3 , K 0.5 Na 0.5 NbO 3 , and KNbO 3 ) are also included in Figure 2 to point out the peak positions. The samples R1 (K + /Na + = 1), R2 (K + /Na + = 2), and R4 (K + /Na + = 4) had XRD‐detachable phase‐pure NaNbO 3 , which was probably caused by the faster reaction between sodium and niobium in comparison with the one between potassium and niobium, as previously seen 30,37 . The higher diffusivity of sodium ions compared to that of potassium was reported for the plausible explanation 47,48 .…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…The ICDD database of the three discrete niobate phases (NaNbO 3 , K 0.5 Na 0.5 NbO 3 , and KNbO 3 ) are also included in Figure 2 to point out the peak positions. The samples R1 (K + /Na + = 1), R2 (K + /Na + = 2), and R4 (K + /Na + = 4) had XRD‐detachable phase‐pure NaNbO 3 , which was probably caused by the faster reaction between sodium and niobium in comparison with the one between potassium and niobium, as previously seen 30,37 . The higher diffusivity of sodium ions compared to that of potassium was reported for the plausible explanation 47,48 .…”
Section: Resultssupporting
confidence: 69%
“…It was previously demonstrated that the monoclinic KNN‐hydrate phase composes of two octahedron layers and one layer of water akin to bismuth‐layered structures (see Figure 7). 67,76 Such layered arrangement allows the formation of primary crystals via the path () 37,41–43,59,67,74 and subsequent growth along with the layer directions 76 3normalNb2O5+8normalOHnormalNb6O198+4H2normalO\begin{equation}3{\rm{N}}{{\rm{b}}_2}{{\rm{O}}_5} + 8{\rm{O}}{{\rm{H}}^ - } \to {\rm{N}}{{\rm{b}}_6}{\rm{O}}_{19}^{8 - } + 4{{\rm{H}}_{\rm{2}}}{\rm{O}}\end{equation} Nnormalb6normalO198+88xnormalK++8xNnormala++nnormalH2OnormalK88xNnormala8xNnormalb6normalO19.nnormalH2O\begin{eqnarray} && {\rm{N}}{{\rm{b}}_6}{\rm{O}}_{19}^{8 - } + \left( {8 - 8x} \right){{\rm{K}}^ + } +\, 8x{\rm{N}}{{\rm{a}}^ + } + n{{\rm{H}}_{\rm{2}}}{\rm{O}} \nonumber\\ && \quad\quad\to {{\rm{K}}_{8 - 8x}}{\rm{N}}{{\rm{a}}_{8x}}{\rm{N}}{{\rm{b}}_{\rm{6}}}{{\rm{O}}_{19}}.n{{\rm{H}}_{\rm{2}}}{\rm{O}}\end{eqnarray} normalK88xNnormala8xNnormalb6normalO19.nnormalH2O6normalK1xN…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations